1989
DOI: 10.1172/jci114223
|View full text |Cite
|
Sign up to set email alerts
|

Localization of transforming growth factor alpha and its receptor in gastric mucosal cells. Implications for a regulatory role in acid secretion and mucosal renewal.

Abstract: Transforming growth factor a (TGFa) shares with epidermal growth factor (EGF) structural homology (35%), a common cell-surface membrane receptor (TGFa/EGF receptor), and a nearly identical spectrum of biological activity, including inhibition of gastric acid secretion. Herein, we report expression of TGFa mRNA in normal gastric mucosa of the adult guinea pig, rat, and dog. TGFa mRNA was also detected in matched surgically resected gastric mucosa and adjacent gastric carcinoma from 10 patients, and in gastric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(90 citation statements)
references
References 50 publications
2
85
0
1
Order By: Relevance
“…Reg may drive 'downward' differentiation, while TGFa may drive 'upward' differentiation. TGFa also has been shown to be upregulated following acute gastric injury (Beauchamp et al, 1989;Polk et al, 1992). During the healing stage of the gastric mucosal lesion, balanced production of the two growth factors might be maintained, in order to reconstruct the properly organized epithelial structure.…”
Section: Discussionmentioning
confidence: 99%
“…Reg may drive 'downward' differentiation, while TGFa may drive 'upward' differentiation. TGFa also has been shown to be upregulated following acute gastric injury (Beauchamp et al, 1989;Polk et al, 1992). During the healing stage of the gastric mucosal lesion, balanced production of the two growth factors might be maintained, in order to reconstruct the properly organized epithelial structure.…”
Section: Discussionmentioning
confidence: 99%
“…Several growth factors including epidermal growth factor (EGF) (Nakano et al, 1995), transforming growth factor (TGF)-a (Sawaoka et al, 1999), basic ®broblast growth factor (Sasaki et al, 1998), and hepatocyte growth factor (Jones et al, 1999) have been shown to stimulate expression of an inducible COX isoform, termed COX-2, in guinea-pig gastric mucosal cells and rat gastric epithelial RGM1 cells, suggesting involvement of COX-2 in prostaglandin generation upon stimulation with these growth factors. Among these growth factors, TGF-a is produced by gastric epithelial cells (Beauchamp et al, 1989), and stimulates prostaglandin generation in the cells (Sawaoka et al, 1999). Furthermore, exogenous prostaglandin activates gastric ®broblasts to stimulate expression of hepatocyte growth factor (Takahashi et al, 1996), which induces proliferation of gastric epithelial cells (Takahashi et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical studies conducted in the gastric mucosa of both mice and humans have demonstrated that Shh is expressed in the parietal cells (21), highly specialized gastric epithelial cells, known to produce and secrete growth factors, and regulatory peptides in the gastric mucosa (21,31,32). Indeed, loss of mature parietal cells, achieved by genetic, pharmacological, and immunological methods, appears to be associated with profound abnormalities in the differentiation and development of multiple cell lineages in the stomach (33)(34)(35)(36)(37).…”
mentioning
confidence: 99%